The association of genetic polymorphisms in interleukin-1 receptors type 1 and type 2 with age-related hearing impairment in a Taiwanese population: a case control study - Ning-Chia Chang; Hua-Ling Yang; Chia-Yen Dai; Wen-Yi Lin; Hsun-Mo Wang; Chen-Yu Chien; Kuen-Yao Ho (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Age-related hearing impairment (ARHI) is a major disability among the elder population. Chronic inflammation is an important factor in the development of ARHI. Interleukin-1 (IL-1) plays a key role in inflammation and may be associated with ARHI. The aim of this study is to analyze the associations of single nucleotide polymorphisms (SNPs) of IL-1 receptor genes with ARHI in an elderly population in Taiwan. Method Participants ≥65 years of age were recruited for audiometric tests and genetic analyses. The bilateral pure-tone average (PTA) of high-tone hearing levels was calculated for ARHI evaluation. The associations of SNPs of the IL-1 receptor type 1 gene (IL1R1) (rs3917225 and rs2234650) and type 2 gene (IL1R2) (rs4141134 and rs2071008) with ARHI were analyzed in 182 ARHI-susceptible (case) and 176 ARHI-resistant (control) participants. Results The G allele of IL1R1 rs3917225 showed a decreased risk of ARHI after adjustments for sex, age, and noise exposure. The GG genotype of IL1R1 rs3917225 in all hereditary models and the TT genotype of IL1R2 rs2071008 in the recessive model also showed decreased risks of ARHI after adjustments. Conclusion These findings suggest that IL1R1 and IL1R2 polymorphisms may contribute to the decreased risk of ARHI in the elderly population.